1996
DOI: 10.1097/00004424-199606000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Metabolic Changes in Chronic Schizophrenia After Neuroleptic Treatment by In Vivo Hydrogen Magnetic Resonance Spectroscopy

Abstract: The current follow-up 1H MR spectroscopy study shows a significant correlation between alterations of (GABA + Glu)/Cr ratio and BPRS, and supports a hypofrontality hypothesis in chronic schizophrenia. The reduction of (GABA + Glu)/Cr ratio after neuroleptic treatment may implicate the recovery of normal neuronal function in neurotransmitters. In vivo 1H MR spectroscopy may be a useful modality in follow-up evaluation of neuroleptic treatment in chronic schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 28 publications
6
70
2
Order By: Relevance
“…However, the Cho/Cr values showed difference with a p value of 0.03. The ratios computed with the RBFNN also compared favorably with those reported in literature [41][42][43][44][45]. The slight variations in the area ratios between published and our (RBFNN and LF) values are expected, since our values are averaged over all voxels covering different brain tissue types within the VOI whereas the published values are based on single voxel measurements.…”
Section: Human Brain Data-supporting
confidence: 78%
See 1 more Smart Citation
“…However, the Cho/Cr values showed difference with a p value of 0.03. The ratios computed with the RBFNN also compared favorably with those reported in literature [41][42][43][44][45]. The slight variations in the area ratios between published and our (RBFNN and LF) values are expected, since our values are averaged over all voxels covering different brain tissue types within the VOI whereas the published values are based on single voxel measurements.…”
Section: Human Brain Data-supporting
confidence: 78%
“…The mI/Cr ratio obtained by the current analysis (RBFNN and LF) is slightly lower than that reported in literature [42][43][44]. This could be because the mI peak at 3.52 ppm is close to the water peak and the water suppression has a great effect on the quantitative values.…”
Section: Human Brain Data-contrasting
confidence: 77%
“…Choe et al (1996) found low frontal NAA/Cre at baseline with no further reductions after naturalistic treatment with typical and atypical agents (follow-up 1-6 months). Fannon et al (2003) reported reduced medial temporal NAA/Cre at baseline which was no longer statistically different from healthy subjects after 3 months of atypical antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Of these, Choe et al (1996) found no changes in NAA with treatment, whereas Fannon et al (2003) found evidence that atypical antipsychotic treatment was associated with an increase in NAA. Our preliminary report (10 schizophrenia patients from the current sample) suggested NAA reductions with antipsychotic treatment (Bustillo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the levels of glutamate or glutamine could indicate abnormal neurotransmission or altered glial function. The hypothesis that alterations in glutamate and GABA neurotransmission might be corrected with treatments has begun to be evaluated with MRS (71)(72)(73), but a thorough exploration remains to be done. Since some recent novel pharmacotherapies proposed for schizophrenia, glutamate release inhibitors and selective agonists for the GABA A receptors bearing the a2 subunit, directly influence glutamatergic and GABA function (63,74), it is likely that a potential role for MRS in drug development for schizophrenia will receive careful study.…”
Section: Glutamate Glutamine and Gabamentioning
confidence: 99%